Real-life impact of highly effective CFTR modulator therapy in children with cystic fibrosis - Olivier, Margarete; Kavvalou, Alexandra; Welsner, Matthias; Hirtz, Raphael; Straßburg, Svenja; Sutharsan, Sivagurunathan; Stehling, Florian; Steindor, Mathis (Frontiers in Pharmacology, 2023)
Introduction: Recently, cystic fibrosis transmembrane regulator modulator therapy with elexacaftor/tezacaftor/ivacaftor has become available for children with cystic fibrosis (CF) carrying at least one F508del mutation. Objective: To assess the intermediate term effects of elexacaftor/tezacaftor/ivacaftor in children with cystic fibrosis in a real-world setting. Methods: We performed a retrospective analysis of records of children with cystic fibrosis, who started elexacaftor/tezacaftor/ivacaftor between 8/2020 and 10/2022. Pulmonary function tests, nutritional status, sweat chloride and laboratory data were assessed before, 3 and 6 months after the start of elexacaftor/tezacaftor/ivacaftor respectively. Results: Elexacaftor/tezacaftor/ivacaftor was started in 22 children 6–11 years and in 24 children 12–17 years. Twenty-seven (59%) patients were homozygous for F508del (F/F) and 23 (50%) patients were transitioned from ivacaftor/lumacaftor (IVA/LUM) or tezacaftor/ivacaftor (TEZ/IVA) to elexacaftor/tezacaftor/ivacaftor. Overall, mean sweat chloride concentration decreased by 59.3 mmol/L (95% confidence interval: −65.0 to −53.7 mmol/L, p < 0.0001) under elexacaftor/tezacaftor/ivacaftor. Sweat chloride concentration also decreased significantly after transition from IVA/LUM or TEZ/IVA to elexacaftor/tezacaftor/ivacaftor (−47.8 mmol/l; 95% confidence interval: −57.6 to −37.8 mmol/l, n = 14, p < 0.0001). Sweat chloride reduction was more marked in children with the F/F than in those with the F/MF genotype (69.4 vs 45.9 mmol/L, p < 0.0001). At 3 months follow-up, body-mass-index-z-score increased by 0.31 (95% CI, 0.2–0.42, p < 0.0001) with no further increase at 6 months. BMI-for-age-z-score was more markedly improved in the older group. Overall pulmonary function (percent predicted FEV1) at 3 months follow-up increased by 11.4% (95% CI: 8.0–14.9, p < 0.0001) with no further significant change after 6 months. No significant differences were noted between the age groups. Children with the F/MF genotype had a greater benefit regarding nutritional status and pulmonary function tests than those with the F/F genotype. Adverse events led to elexacaftor/tezacaftor/ivacaftor dose reduction in three cases and a temporary interruption of therapy in four cases. Conclusion: In a real-world setting, elexacaftor/tezacaftor/ivacaftor therapy had beneficial clinical effects and a good safety profile in eligible children with cystic fibrosis comparable to previously published data from controlled clinical trials. The positive impact on pulmonary function tests and nutritional status seen after 3 months of elexacaftor/tezacaftor/ivacaftor therapy was sustained at 6 months follow-up.